KANDUNGAN ZAT BESI DAN ASAM GLUTAMAT PADA BUBUK PENYEDAP MADIDIHANG DI KOTA TERNATE - Fadila; Sitti Salmiyah A. Bahruddin; Juhartini; Nurlaila Ekaputri (LPPM Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2024)
Food flavouring is always needed by people to enhance the taste of food. Excessive use of synthetic flavouring (Monosodium Glutamate) over a long period of time, can cause harm to health in the future. For this reason, natural alternative ingredients are needed to replace the function of MSG as a food flavouring. Madidihang fish (yellowfin tuna) is rich in nutrients such as protein, fatty acids, and minerals, which can be used as a natural flavouring base. This study aims to determine the iron and glutamic acid content in madidihang flavouring, using a pre-experimental research method with an alternative one-shot case study design. The sample in this study was a 250 gram sample of madidihang flavouring. The test method for iron parameters was the 18-13-1/MU/SMM-SIG ICP OES method, and glutamic acid with the 18-5-17/MU/SMM-SIG UPLC method. The tests were conducted in the laboratory of PT Saraswanti Indo Genetech, Bogor Indonesia, with 2 replicate tests, namely simplo and duplo tests. The data obtained were processed by calculating the average value, then presented descriptively. The average iron content test result was 4.05 mg/100 g, while the average glutamic acid content was 45,571.63 mg/kg. It is concluded that after going through the processing process, madidihang flavouring contains iron and glutamic acid which is good for consumption and can be used as an alternative to natural flavouring instead of artificial flavouring.